2017
DOI: 10.1155/2017/8148742
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil and Monocyte Bactericidal Responses to 10 Weeks of Low‐Volume High‐Intensity Interval or Moderate‐Intensity Continuous Training in Sedentary Adults

Abstract: Neutrophils and monocytes are key components of the innate immune system that undergo age-associated declines in function. This study compared the impact of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on immune function in sedentary adults. Twenty-seven (43 ± 11 years) healthy sedentary adults were randomized into ten weeks of either a HIIT (>90% maximum heart rate) or MICT (70% maximum heart rate) group training program. Aerobic capacity (VO2peak), neutrophil and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 59 publications
6
66
2
3
Order By: Relevance
“…Evaluated the effect of HIIT in obese women with type 2 diabetes and found an improvement in inflammatory profile through the decreased expression of TLR‐4 and TLR‐2 in the cell surface of lymphocytes and monocytes after 2 weeks of training. Furthermore, HIIT induces immune stimulatory actions such as the increasing potential for CCR5‐mediated chemotaxis and improvements in oxidative burst and phagocytosis of stimulated‐leukocytes …”
Section: Discussionmentioning
confidence: 99%
“…Evaluated the effect of HIIT in obese women with type 2 diabetes and found an improvement in inflammatory profile through the decreased expression of TLR‐4 and TLR‐2 in the cell surface of lymphocytes and monocytes after 2 weeks of training. Furthermore, HIIT induces immune stimulatory actions such as the increasing potential for CCR5‐mediated chemotaxis and improvements in oxidative burst and phagocytosis of stimulated‐leukocytes …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, muscle strength has been shown to be negatively associated with days of having fever . In healthy individuals, both moderate‐intensity as well as high‐intensity interval aerobic training has been shown to lead to an improved neutrophil function , and recent findings show that resistance training can increase the number of neutrophils and lymphocytes after exercise .…”
Section: Introductionmentioning
confidence: 99%
“…A recent example is sprint-interval exercise, also referred to as High Intensity Interval Exercise (HIIE), which, as might be expected, stimulates T cell and Natural Killer cell trafficking, but responses are larger following a continuous and sustained exercise stimulus [33]. Other studies have shown that frequent HIIE (or High Intensity Interval Training; HIIT) does not compromise mucosal immunity [34] and that both HIIT and continuous training similarly improve innate immune cell function at rest [35]. Exploring the immunological effects of different exercise modes has merit for improving understanding of immune function, especially if the optimal mode of exercise is yet to be established for particular groups (e.g.…”
Section: Questions That Remain Unanswered: Future Research For Examinmentioning
confidence: 99%